2015
DOI: 10.1177/230949901502300101
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma versus Corticosteroid Injection for Recalcitrant Lateral Epicondylitis: Clinical and Ultrasonographic Evaluation

Abstract: PRP appeared to enable biological healing of the lesion, whereas CS appeared to provide short-term, symptomatic relief but resulted in tendon degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 27 publications
3
118
0
4
Order By: Relevance
“…Furthermore, PRP demonstrated better outcomes at 2 years (P< 0.0001). In another trial in 2013 [11][12][13], CSI resulted in better outcomes at 1 month (P<0.003), with no difference between PRP and CSI groups at 3 months (P = 0.717). In the study in 2015 [12], PRP had better outcomes in comparison with CSI at 6 months (P<0.001).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, PRP demonstrated better outcomes at 2 years (P< 0.0001). In another trial in 2013 [11][12][13], CSI resulted in better outcomes at 1 month (P<0.003), with no difference between PRP and CSI groups at 3 months (P = 0.717). In the study in 2015 [12], PRP had better outcomes in comparison with CSI at 6 months (P<0.001).…”
Section: Resultsmentioning
confidence: 96%
“…A peppering technique was used in all of the three trials which applied PRP and CSI, but two trials [11,12] did not specify the number of penetrations performed in the CSI arms. Most researchers in these four trials performed a single skin entry with 5 to 7 peppering penetrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39][40] When the studies in which PRP was obtained from autologous blood in clinics were considered, it was found that it was prepared from 10 to 20 min. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Nevertheless, it takes time to apply it to cases, which makes its bioactive and effective treatment results controversy.…”
Section: -2234mentioning
confidence: 99%
“…6 For this very reason, it is applied in all fields of medicine including orthopaedic surgery in tissue damage treatments. 7,8 PRP's use has been increasing in many cases such as primarily osteoarthritis, 9 proximal hamstring, 10 Achilles, 11 patellar tendinopathies, 12 talar osteochondral lesions, 13 rotator cuff damage repair, 14 lateral epicondylitis treatment, 15 relieving pains following arthroplasty 8 and contributing to bone healing of tibia in distraction osteogenesis. 8 However, as there are contradictory results reported in some cases in literature where PRP was applied, there are some questions regarding the efficiency of PRP treatment.…”
Section: Introductionmentioning
confidence: 99%